ANALISIS HUKUMAN KEPADA ANAK PELAKU TINDAK PIDANA KEKERASAN MEMAKSA ANAK MELAKUKAN PERSETUBUHAN (Studi Putusan Nomor 5/Pid.Sus.Anak/2017/PN. Trt) - Lishidayanti Dachi (Jurnal Panah Hukum, 2023)
Children are the hope of a family who will become offspring and future, therefore they must be nurtured, educated, guarded and shaped both mentally and in character. Then the child is also the next generation of the result of intercourse of men and women both in marriage and outside marriage. As a result of the lack of supervision of children, it is not uncommon for children to become victims and perpetrators of criminal acts. One form of crime that is often experienced by children is the crime of sexual intercourse. Based on this background, the authors are interested in conducting research with the title Analysis of Sentences to Children Perpetrators of Criminal Acts of Violence Forcing Children to Have Sex (study of decision number 5/Pid.Sus.anak/2017/PN Trt). The type of research used is normative legal research with a statutory approach, case approach, and analytical approach. Data collection is done by collecting data and analyzing secondary data consisting of primary materials, secondary materials, and tertiary materials. The data analysis used is descriptive qualitative analysis and the conclusion is drawn using the deductive method. Based on the research and discussion, it can be concluded that the punishment of children who are perpetrators of violent crimes forcing children to have intercourse (study of decision number 5/Pid.Sus.anak/2017/PN Trt) is that based on a statement of peace that has been agreed upon by the families of both parties which is the most basic reason for the judge to impose sanctions on children Dony Manalu als Dony. This shows that in the decision put forward restorative values ​​or restorative justice. The author suggests that the judge in giving a sentencing decision should pay attention and consider whether the decision is very fair for both the victim and the perpetrator